Between Erudition and Faith. Jean-Jacques Chifflet's Tract on the Shroud of Besançon (1624) Between Erudition and Faith - Paola von Wyss-Giacosa (Journal for Religion, Film and Media, 2019)
The shroud of Besançon, a large cloth considered being a precious relic, an "imprint" left by Christ's body on his burial linen, knew a period of intense veneration and public debate from the early 16th century to the end of the 18th century. With the publication of De linteis sepulchralibus Christi servatoris crisis historica (Antwerp, 1624), a treatise that was as erudite as it was intellectually and conceptually biased, the Bisontine author Jean-Jacques Chifflet significantly contributed to his local shroud's perception and reception. A noteworthy selection of visual material, among it the very first reproduction of the shroud of Besançon in a print medium, was an important part of the book's argument. The present article offers a close reading of parts of Chifflet's treatise, with a particular attention given to the author's targeted use of engravings as illustrationes (images meant to, quite literally, illuminate the text, its meaning and intention), thus looking at this representation of a local relic as a part and as a product of a cultural practice and of shared notions.